O estatuto científico da ciência cognitiva em sua fase inicial uma análise a partir da Estrutura das revoluções científicas de Thomas Kuhn - Alves, Marcos Antonio (Editora Oficina Universitária, 2021)
The objective of this work is to verify the status of cognitive science in its formation, more specifically, between the years 1940 and 1970. Would it have started as pre-science or would it have already established itself as normal science? To answer this question, the authors present the emergence of this area of research in two contexts: historical and epistemological. Having done this, they analyze, based on the conceptual framework of Thomas Kuhn's Structure of Scientific Revolutions, the scientific statute of cognitive science in its initial phase.